Interoception Drives Increased Rational Decision-Making in Meditators Playing the Ultimatum Game - Kirk, Ulrich; Downar, Jonathan; Montague, P Read (Frontiers in Neuroscience, 2011)
Human decision-making is often framed as a competition between cognitive and emotional processes in the brain. Deviations from rational processes are believed to derive from inclusion of emotional factors in decision-making. Here, we investigate whether a group of experienced Buddhist meditators are better equipped to regulate emotional processes compared with controls during economic decision-making in the Ultimatum Game. We show that meditators accept unfair offers on more than half of the trials, whereas controls only accept unfair offers on one-quarter of the trials. By applying fMRI we show that controls recruit the anterior insula during unfair offers. Such responses are powerful predictors of rejecting offers in social interaction. By contrast, meditators display attenuated activity in high-level emotional representations of the anterior insula and increased activity in the lower-level interoceptive representations of the posterior insula. In addition we show that a subset of control participants who play rationally (i.e. accepts >85% unfair offers) recruits the DLPFC reflecting increased cognitive demands to accept unfairness, whereas rational meditators by contrast activates the somatosensory cortex and posterior superior temporal cortex (pSTC). In summary, when assessing unfairness, meditators activate a different network of brain areas compared with controls enabling them to uncouple negative emotional reactions from their behavior. These findings highlight the clinically and socially important possibility that sustained training in mindfulness meditation may impact distinct domains of human decision-making.